Septum resection in women with a septate uterus: a cohort study. Issue 7 (30th April 2020) - Rikken, J F W; Verhorstert, K W J; Emanuel, M H; Bongers, M Y; Spinder, T; Kuchenbecker, W; Jansen, F W; van der Steeg, J W; Janssen, C A H; Kapiteijn, K; Schols, W A; Torrenga, B; et al.
Abstract: Study question: Does septum resection improve reproductive outcomes in women with a septate uterus? Summary answer: In women with a septate uterus, septum resection does not increase live birth rate nor does it decrease the rates of pregnancy loss or preterm birth, compared with expectant management. What is known already: The septate uterus is the most common uterine anomaly with an estimated prevalence of 0.2–2.3% in women of reproductive age, depending on the classification system. The definition of the septate uterus has been a long-lasting and ongoing subject of debate, and currently two classification systems are used worldwide. Women with a septate uterus may be at increased risk of subfertility, pregnancy loss, preterm birth and foetal malpresentation. Based on low quality evidence, current guidelines recommend removal of the intrauterine septum or, more cautiously, state that the procedure should be evaluated in future studies. Study design, size, duration: We performed an international multicentre cohort study in which we identified women mainly retrospectively by searching in electronic patient files, medical records and databases within the time frame of January 2000 until August 2018. Searching of the databases, files and records took place between January 2016 and July 2018. By doing so, we collected data on 257 women with a septate uterus in 21 centres in the Netherlands, USA and UK. Participants/materials, setting, methods: We included women with a septate uterus, defined by the treating physician, according to the classification system at that time. The women were ascertained among those with a history of subfertility, pregnancy loss, preterm birth or foetal malpresentation or during a routine diagnostic procedure. Allocation to septum resection or expectant management was dependent on the reproductive history and severity of the disease. We excluded women who did not have a wish to conceive at time of diagnosis. The primary outcome was live birth. Secondary outcomes included pregnancy loss, preterm birth and foetal malpresentation. All conceptions during follow-up were registered but for the comparative analyses, only the first live birth or ongoing pregnancy was included. To evaluate differences in live birth and ongoing pregnancy, we used Cox proportional regression to calculate hazard rates (HRs) and 95% CI. To evaluate differences in pregnancy loss, preterm birth and foetal malpresentation, we used logistic regression to calculate odds ratios (OR) with corresponding 95% CI. We adjusted all reproductive outcomes for possible confounders. Main results and the role of chance: In total, 257 women were included in the cohort. Of these, 151 women underwent a septum resection and 106 women had expectant management. The median follow-up time was 46 months. During this time, live birth occurred in 80 women following a septum resection (53.0%) compared to 76 women following expectant management (71.7%) (HR 0.71 95% CI 0.49–1.02) and ongoing pregnancy occurred in 89 women who underwent septum resection (58.9%), compared to 80 women who had expectant management (75.5%) (HR 0.74 (95% CI 0.52–1.06)). Pregnancy loss occurred in 51 women who underwent septum resection (46.8%) versus 31 women who had expectant management (34.4%) (OR 1.58 (0.81–3.09)), while preterm birth occurred in 26 women who underwent septum resection (29.2%) versus 13 women who had expectant management (16.7%) (OR 1.26 (95% CI 0.52–3.04)) and foetal malpresentation occurred in 17 women who underwent septum resection (19.1%) versus 27 women who had expectant management (34.6%) (OR 0.56 (95% CI 0.24–1.33)). Limitations, reasons for caution: Our retrospective study has a less robust design compared with a randomized controlled trial. Over the years, the ideas about the definition of the septate uterus has changed, but since the 257 women with a septate uterus included in this study had been diagnosed by their treating physician according to the leading classification system at that time, the data of this study reflect the daily practice of recent decades. Despite correcting for the most relevant patient characteristics, our estimates might not be free of residual confounding. Wider implications of the findings: Our results suggest that septum resection, a procedure that is widely offered and associated with financial costs for society, healthcare systems or individuals, does not lead to improved reproductive outcomes compared to expectant management for women with a septate uterus. The results of this study need to be confirmed in randomized clinical trials. Study funding/competing interest(s): A travel for JFWR to Chicago was supported by the Jo Kolk Studyfund. Otherwise, no specific funding was received for this study. The Department of Obstetrics and Gynaecology, University Medical Centre, Groningen, received an unrestricted educational grant from Ferring Pharmaceutical Company unrelated to the present study. BWM reports grants from NHMRC, personal fees from ObsEva, personal fees from Merck, personal fees from Guerbet, other payment from Guerbet and grants from Merck, outside the submitted work. The other authors declare no conficts of interest. Trial registration number: N/A